VDC_100103288104.0X000001. Issue 3 (November 2015) - Rusted, Brian
Released in 1954 by the National Film Board of Canada, Corral was Colin Low's debut as a director. Low later became identified with the landmark Challenge for Change films using documentary film as a catalyst for community organizing. Although local folk knowledge is frequent in discussions of documentaries made by the French branch of the NFB, it has been more common to treat the English projects of NFB as romantic evocations of place. Corral is often the exemplary case. This article uses paradigms of performance and practice to consider the embodied knowledge and traditional skills depicted in Corral . The place that Corral performs is characterized by the popular diffusion of traditional vaquero skills from California mixed with embodied practices of ranching in southwestern Alberta.